2016
DOI: 10.4236/psych.2016.79126
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Trait Empathy and Psychological Well-Being in Japanese University Students

Abstract: The Interpersonal Reactivity Index (IRI) is a commonly used instrument for measuring individual differences in trait empathy. It is composed of the following four subscales: Perspective taking; fantasy; empathic concern; and personal distress. Previous studies have reported finding a positive relationship between psychological well-being and perspective taking, but little remains known about the association between psychological well-being and the other IRI subscales. Therefore, in this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Additionally, we also replicated previous findings that revealed that affective empathy was positively linked to stress levels . Overall, the pattern of results obtained between empathy and the different indicators of PWB is consistent with the existing literature on the topic .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Additionally, we also replicated previous findings that revealed that affective empathy was positively linked to stress levels . Overall, the pattern of results obtained between empathy and the different indicators of PWB is consistent with the existing literature on the topic .…”
Section: Discussionsupporting
confidence: 91%
“…age, sex, marital status and occupation). As mentioned, empathy‐related traits such as perspective‐taking (a cognitive component) and personal distress (an affective component) also show significant connections with PWB . Moreover, these empathy‐related traits are intercorrelated with humour styles.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations